Delousing efficiency of farmed ballan wrasse (Labrus bergylta) against Lepeophtheirus salmonis infecting Atlantic salmon (Salmo salar) post-smolts - Leclercq, Eric; Davie, Andrew; Migaud, Herve (Pest Management Science, 2014)
BACKGROUND: Cleaner-fish (wrasse, Labridae) are increasingly deployed within the Atlantic salmon (Salmo salar L.) industry as a biological control against sea-lice (Lepeophtheirus salmonis Krøyer). Two tank-based trials were performed to test the effect of farmed ballan wrasse (Labrus bergylta Ascanius) body mass and supplementary feeding on the delousing of Atlantic salmon post-smolts with an initial infection level of ∼12 lice salmon-1 and a ∼5% wrasse:salmon ratio. RESULTS: Sea-louse levels below 0.5 lice salmon-1 were obtained within 84 h, and preferential preying upon larger motile stages was found. The wrasse body mass and the availability of fresh, opened blue mussels (Mytilus edulis L.) did not significantly affect delousing efficiency. The functional predator response was linear, showing no minimum prey density threshold for sea-louse foraging and no satiation plateau, in spite of the high consumption rates measured. Sea-louse infection levels declined following a one-phase exponential decay model, with a standardised decline time constant of 0.8-1.3% h-1 for each wrasse stocked per 100 salmon. CONCLUSIONS: Farmed ballan wrasse are confirmed as highly effective therapeutic and preventive biological controls against sea-lice. The study supports the current minimum hatchery size target (10 mm total length) and the use of supplementary feeding to sustain the wrasse stocks in operation. The functional predator response and the standardised decline time constant of sea-louse abundance are proposed as useful indicators of delousing efficiency. © 2013 Society of Chemical Industry